How Global Financial Markets Affect Sub-Saharan Africa - Delechat, Corinne (2012)
This paper uses a unique database covering 44 countries in sub-Saharan Africa between 2000 and 2007 to study the determinants of the allocation and composition of private capital flows across countries, as well as channels through which these flows could affect growth. In the sample, the degree of financial market development is an important determinant of the distribution of capital flows across countries, as opposed to property rights institutions. The fairly consistent positive association between net capital flows and growth for sub-Saharan African countries is encouraging, though the data do not allow for making conclusive inferences about a causality relationship.